Region Specific miRNA–mRNA Networks in Gray and White Matter Lesions of Progressive Multiple Sclerosis - Adya Sapra; Nagendra K. Rai; Timothy D. Niepokny; Haley Courtney; Ajai Tripathi; Ranjan Dutta (Annals of Clinical and Translational Neurology, 2026)
ABSTRACT Objective Multiple sclerosis (MS) is a neurodegenerative demyelinating disease of the central nervous system. This study aimed to identify micro‐RNA (miRNA)–mRNA regulatory networks underlying region‐specific molecular mechanisms in white matter and gray matter lesions in progressive MS. Methods Global miRNA and mRNA expression profiling were previously performed on white matter and gray matter lesion tissues from postmortem progressive MS brains. These datasets were integrated using Ingenuity Pathway Analysis (IPA) to identify enriched canonical pathways based on experimentally validated miRNA target genes. Functional effects of selected miRNAs were evaluated in primary oligodendrocyte progenitor cells (OPCs) following miRNA mimic transfection using immunocytochemistry and qPCR. Results Nine miRNAs were commonly dysregulated in both White Matter lesions (WMLs) and Gray Matter lesions (GMLs). Pathway analysis identified two major downstream pathways—cellular senescence and EIF2 signaling—with opposing predicted activation states (activated in White Matter lesions and inhibited in Gray Matter lesions). Among the shared miRNAs, miR‐30a and miR‐100 exhibited opposing expression patterns, with downregulation in GMLs and upregulation in WMLs, and both were predicted to regulate each pathway. Corresponding target genes of these miRNAs were significantly dysregulated in MS lesions. In primary Oligodendrocyte Progenitor Cells, overexpression of miR‐30a or miR‐100 significantly reduced proliferation and impaired differentiation, accompanied by decreased expression of their respective target genes. Interpretation These findings identify miRNAs commonly dysregulated across white matter and gray matter lesions in progressive multiple sclerosis. Furthermore, this study also identifies distinct miRNA–mRNA networks and miRNA‐driven regulatory mechanisms that contribute to region‐specific impairment of oligodendrocyte maturation and remyelination.